2010
DOI: 10.5005/jcdp-11-6-33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Antioxidants on the Microleakage of Resin-Based Composite Restorations after Nonvital Bleaching

Abstract: Aim:The aim of this study was to compare the neutralizing effect of antioxidant agents on the microleakage of dental restorations in nonvital teeth after bleaching with carbamide peroxide. Also assessed was the correlation of the microleakage data between an electrochemical and a staining technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 20 publications
2
18
0
4
Order By: Relevance
“…In addition, unlike previous studies in which 10% CP was used for nonvital bleaching,5,6 the use of a stronger bleaching agent, a mixture of 30% HP and sodium perborate, could be another factor in the delayed antioxidant effect of SA. Although the association of sodium perborate with 30% HP can be more effective in lightening tooth color, it may affect bonding more adversely due to the high concentration of peroxide.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, unlike previous studies in which 10% CP was used for nonvital bleaching,5,6 the use of a stronger bleaching agent, a mixture of 30% HP and sodium perborate, could be another factor in the delayed antioxidant effect of SA. Although the association of sodium perborate with 30% HP can be more effective in lightening tooth color, it may affect bonding more adversely due to the high concentration of peroxide.…”
Section: Discussionmentioning
confidence: 87%
“…It has been reported that the application of sodium ascorbate (SA) antioxidant into the access cavity of intracoronally-bleached tooth allows immediate composite restoration after nonvital bleaching through its ability to remove oxygen radicals 4,5. Notwithstanding the proven efficacy of SA application for the purpose, its effective application duration remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a biocompatible and neutral antioxidant, 10% sodium ascorbate, was shown to be able to remove the residual peroxide and oxygen, so that compromised bonding to bleached tooth structures, such as dentin or enamel, could be reversed. [15][16][17] Furthermore, Moosavi et al [5] demonstrated that the addition of surfactant (0.2% Tween ® 80) to a sodium ascorbate formulation could signifi cantly reduce the microleakage after nonvital bleaching. To our knowledge, only one study [18] has investigated the use of catalase in improving the composite-resin bond strength after tooth bleaching.…”
Section: Effects Of Antioxidants On the Microleakage Of Composite Resmentioning
confidence: 99%
“…Moosavi et al. (44) used this method to evaluate the effect of two antioxidants on leakage during a bleaching procedure. They also compared the results obtained with the electrochemical method with similar results obtained on the same teeth using 0·5% basic fuchsin dye penetration over 24 h and the evaluation of sections at 16× magnification.…”
mentioning
confidence: 99%